2011
DOI: 10.1158/0008-5472.can-10-2670
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cell Inhibition of the IFN Response in Tumor-Bearing Mice

Abstract: Our group and others have determined that immune effector cells from patients with advanced cancers exhibit reduced activation of IFN signaling pathways. We hypothesized that increases in immune regulatory cells termed myeloid derived suppressor cells (MDSC) could interfere with the host immune response to tumors by inhibiting immune cell responsiveness to interferons. The C26 murine adenocarcinoma model was employed to study immune function in advanced malignancy. C26 bearing mice had significantly elevated l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
140
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(150 citation statements)
references
References 41 publications
(50 reference statements)
4
140
0
1
Order By: Relevance
“…MDSC-induced loss of STAT1 activation in response to IFN-a or IFN-g has been reported in a murine adenocarcinoma model (46), further supporting a link between IFN-g signaling and MDSC-derived IL-6. The IFN-g-STAT1 signaling regulates its downstream transcriptional factor, T-bet, which is a critical step in T H 1 differentiation (47).…”
Section: Discussionmentioning
confidence: 58%
“…MDSC-induced loss of STAT1 activation in response to IFN-a or IFN-g has been reported in a murine adenocarcinoma model (46), further supporting a link between IFN-g signaling and MDSC-derived IL-6. The IFN-g-STAT1 signaling regulates its downstream transcriptional factor, T-bet, which is a critical step in T H 1 differentiation (47).…”
Section: Discussionmentioning
confidence: 58%
“…It is also possible that there may be additional immunosuppressive mechanisms that are present in the microenvironment of CTCL patients. For example, previous studies by our group and others have demonstrated alterations in NK-cell signaling because of the presence of suppressive myeloid cells such as myeloid-derived suppressor cells and tumor-associated macrophages in cancer patients, 26 and both populations have been reported among CTCL patients. [27][28][29] Additional checkpoint inhibitors, such as PD-1, CTLA-4, TIGIT, and TIM-3 may also play a role in decreasing NK-cell function in patients, because previous studies demonstrated that these inhibitors may be increased in the presence of IL-15.…”
Section: Discussionmentioning
confidence: 84%
“…reduce the efficacy of immunotherapies by impairing antigen presentation and T cell activation. [26][27][28] We found that MDSCs were a good biomarker of metastatic disease and presented a potent prognostic marker for NKT cell activation therapy. Based on circulating levels of MDSCs, we could track responses to NKT cell activation therapy and identify mice that relapsed.…”
Section: Discussionmentioning
confidence: 93%
“…24 MDSCs can directly suppress CD4 C and CD8 C T cell responses, and indirectly promote immune suppression through the induction of FoxP3 C regulatory T cells. [25][26][27][28] Therefore, immunotherapeutic strategies that target both tumor cells and MDSCs are of particular interest. Given that NKT cells have been shown to regulate MDSC-mediated immune suppression during viral infection, 29 the role of NKT cell activation on cancer-associated immunosuppression requires further investigation.…”
Section: Introductionmentioning
confidence: 99%